The Nameless City - Hicks, Faith Erin (First Second, 2016)
Rat, an orphaned street girl, lives in the city that has been conquered by the Dao who killed her parents. Thirteen-year-old Kaidu is the son of a Dao leader who just arrived in the city for military training. And though Rat initially hates Kaidu and everything he represents, the two become unlikely friends. And when an assassination plot unfolds, the future of the city depends on them working together.